CONTAMINATION OF ESCHERICHIA COLI BACTERIA IN SCHOOL CHILDREN'S FOOD (PJAS) IN CAKUNG DISTRICT ELEMENTARY SCHOOL - Hanifatun Nisa Ath Thoriqoh (Jurnal EduHealth, 2020)
Food is a basic human need that is needed at all times and requires good and correct management so that it does not become a medium of disease transmission. Cakung district is the area with the highest incidence of diarrhea in the age group of 5-9 years in East Jakarta in January-June 2016 with 373 cases. Based on preliminary studies it is known that 87% of snack food in Cakung District elementary school is positively contaminated with E.colibacteria. This study aims to find out the contamination of Escherichia coli bacteria in School Children's Food (PJAS) in Cakung District elementary school in 2016. The research design used is cross sectional. The sample of this study amounted to 60 food handlers taken by cluster sampling. Data analysis is conducted univariate and bivariate using the chi squaretest. The results of this study showed that as many as 45% of PJAS positively contaminated with E.colibacteria. Contamination of E.coli bacteria in food is related to the practice of using food serving aids (p = 0.044), where we store cooked food (p = 0.007) and the way of serving (p = 0.02). However, E.coli bacterial contamination is not associated with the practice of washing hands with soap (p = 1.00), washing equipment (p = 0.783), types of selling facilities (p = 0.775), and the existence of sanitation facilities (1.00). The school is advised to collect traders who sell around the school and conduct coaching and empowerment by providing stimulants in the form of completeness of selling facilities, such as the provision of sanitation facilities and trash cans. In addition, hawker food traders are advised to maintain personal hygiene and the environment around the food processing site to avoid the occurrence of bacterial contamination and other disease agents that can enter the food.